Soil Erosion Processes in the Vîlsan River Watershed and Mitigation Measures - Costinescu Ionuţ-Mădălin (Modelling in Civil Environmental Engineering)
This article is intended to highlight the results of a research carried out on erosion processes in the Vâlsan River watershed in Arges County, Romania. The evolution of the relief fragmentation density in accordance with the general evolution of the hydrographic network, the relief energy as a result of the erosion action on the lithological support, the registered specific soil losses ( t · ha-1· yr-1 ), that are influenced by the slope of the land (%), the volume of liquid runoff (m3 ), the volumes of alluvium on the river basin (m3 ), all of these are the most important parameters that give a true picture of the land degradation and soil loss in the studied river basin. In order to stop the evolution of the gully erosion process there are proposed and designed some hydrotechnical works consisting in gabions, both as check-dams on the gully erosion formations as well as gabion walls for protection of the riverbanks.